PEDAGOGICAL FOUNDATIONS FOR DEVELOPING COGNITIVE ACTIVITY AND CREATIVE THINKING OF PRIMARY SCHOOL STUDENTS THROUGH THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Sanjar Rakhimov (Modern American Journals, 2025)
The article examines the pedagogical foundations for enhancing the cognitive activity and creative thinking of primary school students through the use of information and communication technologies (ICT). It emphasizes the importance of ICT integration into the early stages of education as a means of increasing student engagement, improving the efficiency of the learning process, and fostering higher-order thinking skills. The study discusses theoretical perspectives on cognitive and creative development, explores modern digital tools applicable in the primary school environment, and outlines methodological approaches that align with contemporary pedagogical principles. Special attention is given to the ways in which ICT can be used not only as an auxiliary resource but also as a central element of the educational process, creating opportunities for personalized learning, collaboration, and problem-solving. The findings indicate that the competent use of ICT can significantly influence students’ motivation, adaptability, and readiness for lifelong learning.
Keywords: Cognitive activity, creative thinking, information and communication technologies, primary education, pedagogical foundations, digital learning tools, innovative teaching methods.